Footprint of SO2 in China's international trade and the interregional hotspot analysis. (December 2020) - Chuai, Xiaowei; Lu, Qinli; Li, Jianbao
Abstract: SO2, which is one of key components that can deteriorate the environment, can be relocated by international trade. Based on the EORA, the EDGAR databases and input-output model, this study calculated China's SO2 emissions caused by import and export, and presented a method to exhibit China's export-related SO2 footprint at a high resolution. The results showed that export generated more SO2 emissions than import, and the two both increased rapidly since 1990, but decreased in 2008 and 2010, respectively. Both import- and export-related SO2 emissions were concentrated more in undeveloped regions and several developed countries. High percentage of China's export-related SO2 emissions were mainly observed on the secondary industry activities. The percentages for most sectors increased before 2005 and decreased in 2015. Spatially, the export-related emissions decreased obviously from the southeast to the northwest within China. China's export-related SO2 emissions showed an increasing trend overall during 1990–2012. Areas with increasing emission trends were mainly concentrated in areas where the secondary industries were concentrated, such as the North China Plain. Both the increasing and decreasing areas showed highly significant changing trends. The east and south showed intensive distributions of the highly significant changing trends. Highlights: The export activities generated much higher SO2 emissions than imports. Trade pulled SO2 emissions were more concentrated in undeveloped regions. Export-related emissions were more concentrated in the secondary industry. Export-related emissions decreased obviously from the southeast to the northwest. The North China Plain had high emission intensities and an intensive distribution.